ECONOMETRIC MODEL OF OPERATING JOINT-STOCK COMPANY " UZBEKISTON TEMIR YULLARI" AND POSSIBLE DIRECTIONS OF DEVELOPMENT - Abdukadirovna, Mahkamova Mamlakat; Sobirkhuja ugli, Saitkamolov Mukhammadkxuja; Kayumovich, Ishakov Abdulakhat; Yuldashevich, Soatov Fozil; Yuldashevich, Soatov Fozil; Gaybullayevna, Rakhmatova Masuda; Abdusattorovna, Asimova Feruza (International Journal of Psychosocial Rehabilitation, 2020)
–The article analyzes the current state and future development of railway transport, presents an econometric model of the development of investment activity in the context of strategic changes in the transport system. The article is devoted to the substantiation of approaches to the development of an algorithm for assessing the impact of railway transport on the country’s economic security. The proposals on the use of econometric modeling to develop a simulation model of the railway system are justified. The stages of the implementation of the economic feasibility of management decisions in the railway system are considered.Therefore, the priority tasks of the structural reform of the industry is to create conditions for the development of competition in the field of transportation of goods and passengers, repair of rolling stock, as well as increasing investment attractiveness. As a result of the implementation of the planned infrastructure projects, there is an acute problem of a lack of investment funds, and even escalates due to the growing physical depreciation of fixed assets. Currently, there is a big gap between the level of investment existing in the industry and the level necessary to ensure sustainable development.